Design of English Corner Extracurricular Activities in the 4.0 Industrial Revolution Era at Madrasah Ibtida'iyah - Rif’an Humaidi; Amelia Vikri Laili (EDUCARE: Journal of Primary Education, 2022)
English Corner extracurricular activities are one of the choices for students to be able to learn English with more fun. Through the English Corner extracurricular program, the Madrasah provides provisions for its students to face the era of the industrial revolution 4.0. The purpose of this research is to add insight and to know the mechanism of the English corner extracurricular through the development, implementation, assessment, and evaluation of the English corner extracurricular in the 4.0 revolution era at MI Roudlotul Ulum Banyuwangi. This type of research is qualitative research with a descriptive design. Data collection techniques using interviews, observation, and documentation. Data analysis used the concept of Miles and Huberman. The validity of the data was measured by means of triangulation of sources and techniques. The results showed that 1). The development of the English corner extracurricular in facing the 4.0 industrial revolution pays attention to human resources, needs, infrastructure, talents, and interests. 2). The implementation of the English corner extracurricular is almost the same as learning in general and is made more relaxed so that it is more comfortable in its implementation. 3). This English corner extracurricular assessment uses a written manual assessment, after which it is recapitulated and entered into the Digital Report Card Application (ARD). 4). This English corner extracurricular evaluation is carried out every six months or at the end of the semester, taking into account the development and implementation that was carried out in the previous semester.  Kegiatan ekstrakurikuler English Corner menjadi salah satu pilihan peserta didik untuk dapat mempelajari Bahasa Inggris dengan lebih menyenangkan. Melalui program ekstrakurikuler english corner, Madrasah tersebut memberikan bekal kepada siswanya untuk menghadapi era revolusi industri 4.0. Tujuan penelitian ini untuk menambah wawasan serta mengetahui mekanisme ekstrakurikuler english corner melalui pengembangan, pelaksanaan, penilaian, dan evaluasi ekstrakurikuler english corner pada era revolusi 4.0 di MI Roudlotul Ulum Banyuwangi. Jenis penelitian ini ialah penelitian kualitatif dengan desain deskriptif. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Analisis data menggunakan konsep Miles dan Huberman. Keabsahan datanya diukur dengan cara triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa 1). Pengembangan ekstrakurikuler english corner dalam menghadapi revolusi industri 4.0 ini memperhatikan sumber daya manusia, kebutuhan, sarana prasarana, bakat dan minat. 2). Pelaksanaan ekstrakurikuler english corner hampir sama dengan pembelajaran pada umumnya dan dibuat lebih santai agar lebih nyaman dalam penyelenggaraannya. 3). Penilaian ekstrakurikuler english corner ini menggunakan penilaian manual yang tertulis, setelah itu direkap dan dimasukkan dalam Aplikasi Raport Digital (ARD). 4). Evaluasi ekstrakurikuler english corner ini dilakukan setiap 6 bulan sekali atau pada akhir semester, dengan memperhatikan pengembangan dan pelaksanaan yang telah dilakukan pada semester sebelumnya.